A chemical study of the essential oil of Eugenia caryophyllus (Sprengel) Bullock et Harrison (formerly eugenia caryophyllata thunberg) (Family Myrtaceae) - Anulude, Jonathan Ijeoma; Leonido, Rosita (Quezon City Department of Pharmacy, College of Pharmacy, University of the Philippines Diliman, 1977)
A colorless essential oil which turned pale yellow after it had been kept for some time was obtained from the dried flower buds of Eugenia caryophyllus (Sprengel) Bullock et Harrison (formerly known as Eugenia caryophyllata Thunberg; Family Myrtaceae). Oil yield was 13.6% (v/w). The physicochemical properties of the oil are the following: specific gravity = 1.056; Refractive index (n=25/D) = 1.5316; Optical rotation (∝=25/D) = -0°25?. A component isolated by column chromatography showed much similarities with Eugenol.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Diliman, 1977.
Keywords: Essences and essential oils; Clove tree